2014
DOI: 10.3390/nu6093516
|View full text |Cite
|
Sign up to set email alerts
|

Is the Inclusion of Animal Source Foods in Fortified Blended Foods Justified?

Abstract: Fortified blended foods (FBF) are used for the prevention and treatment of moderate acute malnutrition (MAM) in nutritionally vulnerable individuals, particularly children. A recent review of FBF recommended the addition of animal source food (ASF) in the form of whey protein concentrate (WPC), especially to corn-soy blends. The justification for this recommendation includes the potential of ASF to increase length, weight, muscle mass accretion and recovery from wasting, as well as to improve protein quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…In the larger context of the operational costs of a supplementary feeding program that includes staff, anthropometric equipment, logistical support, and facilities, this additional cost is quite minimal for the significantly higher recovery rate achieved. Although some have questioned whether the benefits of including dairy protein are worth the additional expense (6), this study provides evidence that their inclusion leads to improved outcomes in children with MAM with only a marginal increase in cost.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the larger context of the operational costs of a supplementary feeding program that includes staff, anthropometric equipment, logistical support, and facilities, this additional cost is quite minimal for the significantly higher recovery rate achieved. Although some have questioned whether the benefits of including dairy protein are worth the additional expense (6), this study provides evidence that their inclusion leads to improved outcomes in children with MAM with only a marginal increase in cost.…”
Section: Discussionmentioning
confidence: 75%
“…Whereas previous studies have shown positive correlations between the consumption of dairy protein and improved outcomes in undernourished populations (8-10), it was unclear whether those findings specifically were due to the type of protein in the food or simply the total amount of protein (6). Despite providing 33% less total protein and nearly 8% less total energy, outcomes were better in children receiving whey RUSF than in those receiving soy RUSF.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Dietary variety beyond food aid may contribute to these findings as well. A 2014 review found that FBF containing isoenergetic, isonitrogenous sources of animal-source proteins did not enhance linear growth compared with plant proteins, suggesting that animal protein itself may not be needed to be included in FBF ( 17 ) . While total weight gained is used as a surrogate for protein efficiency, studies have also supported that weight gain is not an accurate surrogate for prevention of stunting, more accurately depicted by linear growth.…”
Section: Discussionmentioning
confidence: 99%
“…This process precooks FBFs, meaning that they require less time and resources to prepare. It has also been suggested that animal-source protein, such as whey protein concentrate (WPC), be included in FBFs (6); however, its costly inclusion has been questioned (11, 12). Plant protein alternatives, such as soy protein isolate (SPI), may be a less-expensive option that leads to similar product and nutritional outcomes (13).…”
Section: Introductionmentioning
confidence: 99%